Department Of Business Management University Of Alberta Public University In Edmonton, Canada - Azizbek Yokubjonovich Nazarov (International Scientific and Current Research Conferences, 2021)
This article is devoted to the study of archival funds kept in the National Archives of Uzbekistan by scientific societies operating in the Turkestan region in the late XIX - early XX centuries. The article examines the status of documents that contain information about the emergence and activities of scientific societies. The condition of the papers in the archives is analyzed.